Case report: A heterozygous mutation in ZNF462 leads to growth hormone deficiency - Zhou, Yikun; Liu, Jianmei; Wu, Shuai; Li, Wanran; Zheng, Yun (Frontiers in Genetics, 2022)
Weiss-Kruszka syndrome (WSKA) is a rare disease, most often caused by mutations of the ZNF462 gene. In order to screen for hereditary diseases, the exons of the patient’s genome were sequenced. Genomic PCR experiments followed by Sanger sequencing was used to confirm the mutated genomic regions of the patient and his parents. We reported a new mutation site, a heterozygous mutation (NM_021224.6:c.6311dup) in ZNF462 in a male patient of 8 years old. The mutation in ZNF462 gene caused WSKA. This patient is the first case with WSKA characterized by attention deficit hyperactivity disorder (ADHD) and complete growth hormone deficiency (GHD) without pituitary lesions. Our results suggest that the heterozygous mutation in ZNF462 is the direct cause of WSKA of this patient. The mutations in other genes interacting with ZNF462 result in similar symptoms of WSKA. Furthermore, ZNF462 and its interacting proteins ASXL2 and VPS13B may form a protein complex that is important for the normal development and still awaits more studies to reveal its detailed functions.